2020
DOI: 10.24127/ajpm.v9i1.2589
|View full text |Cite
|
Sign up to set email alerts
|

The Self Regulated Learning, Habit of Mind, and Creativity as High Order Thinking Skills Predictors

Abstract: Tujuan penelitian ini adalah untuk menunjukkan bahwa kemandirian belajar, kebiasaan berpikir, dan kreativitas dapat dijadikan sebagai prediktor terhadap kemampuan berpikir tingkat tinggi. Metode penelitian ini menggunakan metode kuantitatif dengan bentuk penelitiannya berupa penelitian ex post facto. Teknik pengumpulan data yang digunakan adalah teknik pengukuran dan komunikasi tidak langsung sehingga alat pengumpul data yang digunakan adalah tes HOTS dan angket. Populasi dalam penelitian ini adalah seluruh ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 2 publications
0
5
0
3
Order By: Relevance
“…The weak ability of students to solve a problem can be sourced from students' thinking habits (Pei et al, 2018;Umar, 2017). Students' thinking habits in dealing with and solving a problem will make students accustomed to finding new problems every time (Hodiyanto & Firdaus, 2020;Papadopoulos, 2019). This shows that students' Habits of Mind have an important role in the learning process of individual development in helping to solve a problem.…”
Section: Introductionmentioning
confidence: 99%
“…The weak ability of students to solve a problem can be sourced from students' thinking habits (Pei et al, 2018;Umar, 2017). Students' thinking habits in dealing with and solving a problem will make students accustomed to finding new problems every time (Hodiyanto & Firdaus, 2020;Papadopoulos, 2019). This shows that students' Habits of Mind have an important role in the learning process of individual development in helping to solve a problem.…”
Section: Introductionmentioning
confidence: 99%
“…Prodi PPKn senantiasa perlu mengembangkan kemandirian mahasiswa, karena mempersiapkan mereka menjadi pendidik yang berkualitas, kreatif, dan adaptif. Kemandirian yang didukung oleh HOTS tidak hanya meningkatkan efektivitas belajar dan mengajar tetapi juga membentuk karakter dan kepribadian yang kuat, yang sangat penting dalam pendidikan (Hodiyanto & Firdaus, 2020). Dengan kemandirian yang dimiliki, calon pendidik dapat menghadapi tantangan dunia pendidikan yang semakin berkembang dan memberikan kontribusi positif bagi masyarakat dan negara.…”
Section: Pendahuluanunclassified
“…Laia's research also revealed that social interaction with peers in the learning process can be developed by mathematical resilience skills in the learning process (Liew et al, 2018). Furthermore, The results of research conducted by Hodiyanto and Firdaus (2020) reveal that habits of mind contribute to students' creative thinking abilities which are built by a process of social interaction in the mathematics learning process. Research conducted by Levasseur and Cuoco (2003) found habits of mind determine interaction behavior that can reduce memory workload in the process of learning mathematics.…”
Section: Introductionmentioning
confidence: 97%
“…Mathematical resilience and habits of mind aim to develop thinking skills in dealing with mathematical problems (Chusna et al, 2021;Hodiyanto & Firdaus, 2020). The process of solving mathematical problems in learning is inseparable from how the interaction process occurs in learning (Wu et al, 2019).…”
Section: Introductionmentioning
confidence: 99%